2021
DOI: 10.3342/kjorl-hns.2020.00731
|View full text |Cite
|
Sign up to set email alerts
|

The Recovery of Odontogenic Sinusitis after Endoscopic Sinus Surgery

Abstract: Background and Objectives The present study was designed to investigate the normalization period of the maxillary sinus after endoscopic sinus surgery (ESS) for odontogenic sinusitis (ODS) and factors related to it. The thickness of the maxillary sinus mucosa may reflect the improvement of symptoms and may help determine when the dental implant procedure will be possible. Subjects and Method A total of 52 patients (34 males and 18 females) who were diagnosed with ODS and treated by ESS between 2014 and 2019 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…There are also publications on the successful results of SGB application in cases with olfactory sensory impairment due to different etiological conditions [22][23][24]. A study by Lee et al [25] showed that superior cervical ganglionectomy enhanced the regeneration of olfactory receptor cells in zinc sulfate-induced mouse anosmia. Ho Sik Moon et al [22] reported that of 37 patients with anosmia or hyposmia with different etiologies, 15 (40.5%) responded to SGB with significant improvement in their symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…There are also publications on the successful results of SGB application in cases with olfactory sensory impairment due to different etiological conditions [22][23][24]. A study by Lee et al [25] showed that superior cervical ganglionectomy enhanced the regeneration of olfactory receptor cells in zinc sulfate-induced mouse anosmia. Ho Sik Moon et al [22] reported that of 37 patients with anosmia or hyposmia with different etiologies, 15 (40.5%) responded to SGB with significant improvement in their symptoms.…”
Section: Discussionmentioning
confidence: 99%